Managing wildfire disasters in the Rocky Mountains. Issue 2 (22nd March 2019) - Craig, Christopher
Abstract : Research methodology: The paper employs ethnographic interviews, a quantitative and qualitative data analysis of publicly accessible data and literature review. Case overview/synopsis: With drought conditions expected to worsen in at-risk areas thus amplifying wildfire likelihood, this case explores the organizational and natural dynamics involved with wildfire management. The case engages students to explore the interactions between wildfire, wildland firefighters and agency organizations drawing from the natural resource dependence theory within a sustainability context. When completing the discussion questions, students are challenged to explore how organizations can use discursive closures to eliminate conflict and control meaning surrounding potentially controversial and politicized topics such as wildfire management. Complexity academic level: This interdisciplinary case would be appropriate for undergraduate and graduate students in business and STEM classes. Optimal classes include organizational behavior, organizational communication and sustainability. Other appropriate classes include strategic management, applied business decisions, public relations, public policy, crisis management and for corporate training purposes.